2012
DOI: 10.1371/journal.pone.0049345
|View full text |Cite
|
Sign up to set email alerts
|

Rationale-Based Engineering of a Potent Long-Acting FGF21 Analog for the Treatment of Type 2 Diabetes

Abstract: Fibroblast growth factor 21 (FGF21) is a promising drug candidate for the treatment of type 2 diabetes. However, the use of wild type native FGF21 is challenging due to several limitations. Among these are its short half-life, its susceptibility to in vivo proteolytic degradation and its propensity to in vitro aggregation. We here describe a rationale-based protein engineering approach to generate a potent long-acting FGF21 analog with improved resistance to proteolysis and aggregation. A recombinant Fc-FGF21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
178
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(186 citation statements)
references
References 27 publications
(43 reference statements)
8
178
0
Order By: Relevance
“…Several pharmaceutical companies thus focused on improving various properties of human FGF21 protein to make it suitable for therapeutic development. The native mature form of FGF21 is a 19.4 kDa protein that is cleared rapidly from circulation most likely through the kidney, and has an estimated half-life of ∼1 h in rodents and 0.5-2 h in NHPs [31], [68]. In addition to the rapid renal clearance, human FGF21 protein undergoes rapid proteolysis upon injection into animals so that the 4 N-terminal amino acid residues [69] and the C-terminal 10 amino acid residues are cleaved off [68].…”
Section: Turning Fgf21 Into a Drugmentioning
confidence: 99%
See 1 more Smart Citation
“…Several pharmaceutical companies thus focused on improving various properties of human FGF21 protein to make it suitable for therapeutic development. The native mature form of FGF21 is a 19.4 kDa protein that is cleared rapidly from circulation most likely through the kidney, and has an estimated half-life of ∼1 h in rodents and 0.5-2 h in NHPs [31], [68]. In addition to the rapid renal clearance, human FGF21 protein undergoes rapid proteolysis upon injection into animals so that the 4 N-terminal amino acid residues [69] and the C-terminal 10 amino acid residues are cleaved off [68].…”
Section: Turning Fgf21 Into a Drugmentioning
confidence: 99%
“…The native mature form of FGF21 is a 19.4 kDa protein that is cleared rapidly from circulation most likely through the kidney, and has an estimated half-life of ∼1 h in rodents and 0.5-2 h in NHPs [31], [68]. In addition to the rapid renal clearance, human FGF21 protein undergoes rapid proteolysis upon injection into animals so that the 4 N-terminal amino acid residues [69] and the C-terminal 10 amino acid residues are cleaved off [68]. In vitro studies using recombinant truncated proteins showed that while the 4 N-terminal amino acid residues are not necessary for the signaling activity, the C-terminal 10 amino acid residues are essential for binding to KLB and signaling activity [43], [70].…”
Section: Turning Fgf21 Into a Drugmentioning
confidence: 99%
“…Site-specific conjugation of 30-kDa polyethylene glycol to FGF21 demonstrated 10-to 50-fold improvements in CL/F compared with rFGF21, albeit at the expense of 5-to 10-fold reductions in in vitro potency (Mu et al, 2012). Fusion of NT (Fc-FGF21) or CT of FGF21 (FGF21-Fc) to the Fc fragment of hIgG 1 right-shifted in vitro potency 2-to 4-fold and 1000-fold, respectively (Hecht et al, 2012). The slightly reduced in vitro potency of Fc-FGF21 was offset by a 30-fold increase in serum persistence.…”
Section: Introductionmentioning
confidence: 99%
“…Native FGF21 has a very short half-life and is cleared predominantly by renal excretion after administration (Hager et al, 2013). To attempt to create a longer-acting therapeutic, FGF21 was initially recombinantly fused to the C terminus of human Fc (Hecht et al, 2012). However, by using differential enzyme-linked immunosorbent assay coupled with ligand-binding MS, it was found that the C terminus underwent very fast peripheral catabolism at a proline residue 10 amino acids upstream of the terminus.…”
Section: Criticality Of Biotransformation Studies Based On Biotherapementioning
confidence: 99%
“…Since the C terminus of the construct had to remain intact to retain potency, protein engineering efforts were undertaken to stabilize this catabolic liability. After numerous constructs were generated, the construct with this proline mutated to a glycine residue showed retained potency with complete stability against biotransformation in this region (Hecht et al, 2012;Hager et al, 2013). These efforts demonstrated the necessity of understanding biotransformation, using this information to stabilize the molecule for retained potency and decreased clearance, and selecting the proper LBA to track only the bioactive entities during PK profiling.…”
Section: Criticality Of Biotransformation Studies Based On Biotherapementioning
confidence: 99%